Build Entrepreneurial Interest Through PEKA Analysis on Increasing Students Income of Management Study Program Pamulang University - Nardi Sunardi; Rosa Lesmana (Jurnal SEKURITAS (Saham, Ekonomi, Keuangan dan Investasi), 2023)
The purpose of this study is to determine the influence of PEKA analysis on increasing the income of the students of management study program at Pamulang University, the influence of PEKA analysis on the interest in entrepreneurship of students of management study program at Pamulang University and the influence of interest in entrepreneurship on increasing the income of the students of management study program Pamulang University. This type of research is quantitative. The object of analysis is students of the management study program at Pamulang University for the year of 2022, data were collected through a questionnaire. The analytical method uses SEM analysis and the tool used is lisrel 8.70. The results showed that the PEKA analysis had no effect on increasing the income of the students of management study program Pamulang University, but the PEKA analysis had an effect on increasing the entrepreneurial interest of the students of management study program Pamulang University, and interest in entrepreneurship has no  effect on income increasing of the students  of management study program Pamulang University